The Arab Convention for Combating Terrorism, Iraq as a Model - Salman, Ali Nadhum (International Journal of Psychosocial Rehabilitation, 2020)
Protecting of Human rights and maintaining freedoms are one of the most important priorities of international law in it's branches of international humanitarian law and international law for human rights, in times of peace and war. Security council comes to at the head of the structure of international law in term of protecting humanity. Where this paper shows up in the time of the violations of human rights in the Middle East. Therefore, this paper clarifies the role of the Security Council and international laws as all in the protection of human rights through reference to international conventions, committees, charters and declarations and the role played by the international judiciary in imposing the legal mechanisms that guarantee the maintenance and respect of human right.